A Novel Indolizine Derivative Induces Apoptosis Through the Mitochondria p53 Pathway in HepG2 Cells - Liu, Yushuang; Shao, Enxian; Zhang, Zhiyang; Yang, Daji; Li, Guanting; Cao, Hua; Huang, Hongliang (Frontiers in Pharmacology, 2019)
Indolizine derivatives are a class of compounds with excellent biological activity. In this study, a series of indolizine derivatives compound1 (C1), compound2 (C2), compound3 (C3) and compound4 (C4) were synthesized. MTT assay was used to evaluate their cytotoxicity against HepG2 (p53-wild), A549 and HeLa cell lines. HepG2 cells apoptosis induced by C3 was determined using Hoechst staining and AO/EB staining. Cells apoptotic ratio was measured by Annexin V-FITC/PI double staining. Changes in mitochondrial membrane potential and intracellular reactive oxygen species in HepG2 cells after C3 treatment were determined. Immunofluorescence staining and western blot analysis were carried out to detect p53 levels and analyze the apoptosis-associated proteins, respectively. Moreover, the cytotoxic activity of C3 was examined in two other HCC cell lines with different p53 status including Huh-7 cells (p53-mutant) and Hep3B cells (p53-null). The results indicated that C3 showed stronger inhibition towards HepG2 cells than other cell lines. Fluorescent staining and Flow cytometry analysis confirmed that C3 induced apoptosis of HepG2 cells. C3 could also increase intracellular ROS and cause a decrease in the mitochondrial membrane potential. C3 promoted p53 activation and increased p53 accumulation in nuclear. The expression of p53 and Bax was increased with the down regulation of Bcl-2, which promoted the release of cytochrome c and caspase-3 activation. Collectively, the study demonstrated that C3 caused HepG2 cells apoptosis via mitochondria p53 pathway. These results inspired us to further develop indolizine derivatives as potential potent inhibitors against liver cancer.